The Dynamics of E-Government-Based Administrative Public Services - Andrian Putro, Yusup Lintang Cahyo; Maricar Besa (Universitas Terbuka, 2025)
Adopting e-government in local administration has become a strategic global response to enhance public service efficiency, transparency, and accessibility, particularly in developing countries. This study investigates the implementation of e-government in village governance, using Campurejo Village, Indonesia, as a case study. Employing a qualitative research design, data were collected through in-depth interviews with 18 informants, direct observation, and document analysis. The findings reveal that e-government adoption has improved administrative efficiency and service delivery. However, critical challenges remain, including inadequate digital infrastructure, limited internet access, and low digital literacy; only 44% of village officials possess sufficient IT skills. Moreover, limited public access to village data hinders transparency and civic participation. Campurejo Village has achieved “Independent Village” status despite these constraints, as reflected by a Village Development Index (IDM) score of 0.821. It demonstrates the transformative potential of digital governance in rural areas when supported by strong local leadership and adaptive policy strategies. This study contributes to the growing discourse on digital transformation in public administration by providing empirical insights into grassroots-level governance in decentralized settings. It highlights the importance of capacity-building, policy innovation, and cross-sector collaboration in overcoming local barriers to digital adoption. The findings offer valuable lessons for other rural communities and developing regions aiming to implement e-government systems to support inclusive and sustainable governance.